Retinoic acid regulates gap junction intercellular communication in human endometrial stromal cells through modulation of the phosphorylation status of connexin 43. Issue 4 (20th December 2012) - Wu, Juanjuan; Taylor, Robert N.; Sidell, Neil
Abstract Previous studies revealed that gap junction intercellular communication (GJIC) among uterine stromal cells plays critical roles in modulating decidualization, neovasularization, and embryo implantation. Connexin (Cx) proteins are the major component of gap junctions and Cx43 is the most widely expressed connexin in endometrium. Phosphorylation of Cx43 was found to impair gap junction communication in this tissue. Using primary human endometrial stromal cells (ESCs) and a stable high telomerase‐expressing ESC transfectant (T‐HESC), we found that retinoic acid (RA) altered the phosphorylation status of Cx43 protein such that there was a decrease in the phosphorylated (P1 and P2) species accompanied by an increase in the non‐phosphorylated (P0) form. This process is dependent on protein phosphatase 2A (PP2A) activity since selective PP2A inhibitors prevented the ability of RA to dephosphorylate Cx43. Although RA had no effect on total PP2A expression or activity, it significantly increased the intracellular association of Cx43 and PP2A. Inhibition of transcription and protein synthesis by actinomycin D and cycloheximide, respectively, had no effect on the RA‐induced changes in the Cx43 phosphorylation pattern. Furthermore, BMS493, a potent antagonist of the classical RA‐mediated transcriptional pathway, did not inhibit RA‐induced Cx43 dephosphorylation. Our data indicate that RA stimulates physical association of PP2A with Cx43, resulting in the dephosphorylation of Cx43 and, as a consequence, up‐regulation of GJIC in ESCs. This process is independent of new mRNA and protein synthesis and suggests a novel mechanism by which aberrant retinoid metabolism can explain certain reproductive disorders manifested by dysfunctional endometrial cell GJIC. J. Cell. Physiol. 228: 903–910, 2013. © 2012 Wiley Periodicals, Inc.